SASAK LANGUAGE DEIXIS ON MERIAQ-MERIKU DIALECT IN PENUJAK SOCIETY - Mas'ud, Lalu; Hilmiyatun, Hilmiyatun; Ernawati, Titin (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2020)
Deixis is defined as a demonstrative pronoun that is used to designate a person, place, and time. The use of deixis is commonly found in the Sasak language of the meriaq-meriku dialect in the community of Penujak village in greetings. This research aims to describe the deixis of the Sasak language of meriaq-meriku dialect in the community of Penujak village. The data of this research are speech descriptions that have been transcribed in the form of speech by speakers and interlocutors. The data were obtained from the community that owns and uses the Sasak language of the meriaq-meriqu dialect, namely Penujak village, Praya Barat sub-district, Central Lombok District. The data were collected using the technique of engaging and speaking without observing (simak bebas libat cakap). To ensure the validity of the research data, triangulation was administered as a comparison of the data with the theory used. The data were analyzed using a separate method in the form of elements of language as the object of research objectives. The deixis found in the community of Penujak village are: personal deixis in the form of; É™ku 'I' , tiang 'I' , itÉ™ 'we', lÉ™pÊŠ?tÉ™ 'we all/together', kÉ™mu 'you', sidÉ™ 'you', and nijÉ™/ijÉ™ 'dia'; place deixis in the form of: ija?/nija?/nini 'this/ here', tÉ™ 'there', tuË 'there (far)', and taoh 'there'; and time deixis in the form of: nani â€˜nowâ€™, bÉ™rÊŠ? â€˜just nowâ€™, lawÊŠn â€˜laterâ€™, É”ne? â€˜justâ€™, lÉœma? â€˜tomorrowâ€™, uwÉª? 'yesterday', sÉ™nawah 'three days from now', laÉœ? 'first (related to time) ', and Éœra? 'next day (indefinite time) '. The finding of deixis in the meriaq-meriku dialect is a form of identification of the use of the regional language of the Sasak community in Lombok.Keywords: deixis, Sasak language, meriaq-meriku dialect.